Micro arc oxidation of Ti-15Zr-7.5Mo alloy - Tsutsumi, Yusuke; Ashida, Maki; Nakahara, Kei; Serizawa, Ai; Doi, Hisashi; Grandini, Carlos Roberto [UNESP]; Rocha, Luís Augusto [UNESP]; Hanawa, Takao (Japan Institute of Metals, 2016)
Ti-15Zr-7.5Mo alloy was melted and its structure and mechanical properties were evaluated, followed by micro-arc oxidation (MAO) treatment to add bioactivity. Melted Ti-15Zr-7.5Mo alloy was consisted of mainly β containing of metastable α and ω phases. The Vickers hardness of the alloy was 420 HV and larger than those of Ti-6Al-4V alloy (320 HV) and Ti-29Nb-13Ta-4.6Zr ally (TNTZ) (180 HV). The Young's modulus of the alloy was about 104-112 GPa and almost the same as that of Ti-6Al-4V alloy (113 GPa) and larger than that of TNTZ (80 GPa). The MAO treatment was performed in a mixed electrolyte of 0.1-mol L-1 calcium glycerophosphate and 0.15-mol L-1 calcium acetate with a positive maximum voltage of 400 V and a 31.2 mA cm-2 for 600 s. Porous composite oxide of Ti, Zr, and Mo containing large amounts of Ca and P was formed on Ti-15Zr-7.5Mo alloy by micro arc oxidation (MAO) treatment. Zr was preferentially enriched and Ti and Mo were depleted in the oxide layer. Pore size was larger than that of CP Ti. The ability of calcium phosphate formation of the alloy in Hanks' solution after MAO treatment was less than those of CP Ti and TNTZ. It is necessary for the alloy to conduct a chemical treatment to accelerate bone formation.
Keywords: Bioactivity; Mechanical property; Micro arc oxidation; Structure; β-type titanium alloy